Analysis of Consumer Characteristics on Impulsive Buying Behavior of Fashion Products in the Digital Age - Sudarso , Satrio; Ardiani , Ninda (Indonesian Journal of Innovation Studies, 2026)
General Background: Digital transformation, social media expansion, and e-commerce growth have reshaped consumer behavior, making impulsive buying especially in fashion more prevalent. Specific Background: Fashion items function not only as necessities but also as identity symbols influenced by visual stimuli, promotions, and algorithm-driven advertising. Knowledge Gap: Prior studies seldom integrate technological, psychological, social, and financial factors with consumer engagement to explain impulsive fashion purchases in a digitally dense environment. Aims: This study examines how these consumer characteristics predict impulsive buying behavior among individuals aged 18–35 who actively shop for fashion products online. Results: Findings show that psychological, social, and financial factors significantly affect impulsive buying, while technology plays a lesser role; consumer engagement emerges as the strongest predictor, and the model explains 57% of behavioral variance. Novelty: This research uniquely demonstrates that impulse buying is driven more by affective and social dynamics than by digital convenience, highlighting the mediating intensity of online engagement. Implications: The study suggests that marketers should employ emotionally resonant, socially oriented strategies—such as influencer collaboration and interactive digital promotion—to effectively stimulate impulsive purchasing within fashion markets. Highlights: Impulse buying is driven primarily by psychological, social, and financial factors, not technological convenience. Consumer engagement on social media is the strongest predictor of impulsive fashion purchases. Digital platforms amplify emotional and identity-based triggers, shaping modern buying behavior. Keywords: Impulsive Buying, Fashion Consumers, Social Media Engagement, Psychological Factors, Digital Marketing